The effect of material distribution on the out-of-plane elastic properties of hierarchical diamond honeycombs. (1st December 2022) - Wen, Weibin; Lei, Ming; Tao, Yong
Highlights: A novel hierarchical diamond honeycomb with variable wall thickness (HDH-VT) is proposed based on hierarchical diamond honeycomb (HDH) and natural honeycomb. Theoretical models for the Young's and shear moduli of HDH and HDH-VT are derived and validated. The shear modulus of HDH-VT can be tailored in a wide range by adjusting geometric parameters. Abstract: Inspired by the natural honeycomb structure, a novel bio-inspired hierarchical diamond honeycomb with variable wall thickness (HDH-VT) is proposed by introducing a bio-inspired material distribution design into hierarchical diamond honeycomb (HDH) in this study. A full-scale finite element technique is proposed to simulate the compression and transverse shear tests and employed to numerically calculate the out-of-plane elastic properties of HDH and HDH-VT. Theoretical models for the out-of-plane Young's and shear moduli of HDH and HDH-VT are developed and validated. The effects of geometric parameters and relative density on the Young's and shear moduli of HDH and HDH-VT are analyzed. The results indicate that the elastic properties of HDH and Young's modulus of HDH-VT are only related to the relative density. In addition, the out-of-plane shear modulus of HDH-VT is significantly affected by the material distribution. The shear modulus of HDH-VT can be widely tailored by adjusting geometric parameters without sacrificing Young's modulus. This study provides a novel strategy for the design of the skin material of morphing aircraft with widely tailorable mechanical properties.